FEATURES OF PROVIDING PSYCHOLOGICAL ASSISTANCE TO MILITARY PERSONNEL WITH SIGNS OF PSYCHOLOGICAL INJURY - Smirnova, Tetiana; Osodlo, Vasyl (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . The war waged by Russia against Ukraine makes extremely difficult demands on the personality of a military personnel. In stressful conditions, his psyche may experience a psycho-traumatic effect. These risks encourage the search for optimal approaches to providing psychological care without waiting for the end of hostilities. In global practice, there are a large number of effective tools for improving the psychophysiological state of military personnel after exposure to excessive stress. A comparison of foreign and domestic approaches to the problem of overcoming the psychotraumatic consequences of war will make it possible to single out the main tasks of providing psychological assistance in today's extremely difficult conditions. The purpose of the article is theoretical substantiation and definition of the main areas of providing psychological assistance to military personnel in the conditions of the Russian-Ukrainian war.M e t h o d s . The theoretical methods of analysis, synthesis and generalization of scientific sources were used to establish the theoretical basis of the research. Empirical research methods were used to determine the specifics of providing psychological assistance to military personnel (observation, experiment, questionnaire and testing).R e s u l t s . The peculiarities of psychological trauma of military personnel, participants of the Russian-Ukrainian war, as well as modern evidence-based methods of providing psychological assistance to military personnel are analyzed. The expediency of providing comprehensive psychological assistance to military personnel with signs of psychological trauma using evidence-based psychotherapy methods was considered.C o n c l u s i o n s . In today's conditions of full-scale armed aggression of the Russian Federation against Ukraine, military personnel of the Armed Forces of Ukraine are exposed to various types of psychological trauma during their continuous participation in hostilities. The main psychotraumatic factors include a constant threat to life and health, captivity and violence, loss, mutilation, neglect by the enemy of the provisions of International Humanitarian Law, etc. These factors lead to an increase in the number of cases of complex post-traumatic stress disorder and increase the need for psychological help, which is confirmed by the results of a psychological study. The analysis of foreign experience shows the success of the early intervention protocols of psychological assistance in the world's leading armies. The use of evidence-based methods of psychological assistance gives a positive result, so this direction of research is promising.
Keywords: psychological help, psychological recovery, combat mental trauma, post-traumatic stress disorder, combat stress